What We Have Learned about Terrorism since 9/11 - Gaibulloev, Khusrav (2019)
This overview examines critically the post-9/11 empirical literature on terrorism. Major contributions by both economists and political scientists are included. We focus on five main themes: the changing nature of terrorism, the organization of terrorist groups, the effectiveness of counterterrorism policies, modern drivers or causes of terrorism, and the economic consequences of terrorism. In so doing, we investigate a host of questions that include: How do terrorist groups attract and retain members? What determines the survival of terrorist groups? Is poverty a root cause of terrorism? What counterterrorism measures work best? In the latter regard, we find that many counterterrorism policies have unintended negative consequences owing to attack transference and terrorist backlash. This suggests the need for novel policies such as service provision to counter some terrorist groups' efforts to provide such services. Despite terrorists' concerted efforts to damage targeted countries' economies, the empirical literature shows that terrorism has had little or no effect on economic growth or GDP except in small terrorism-plagued countries. At the sectoral level, terrorism can adversely affect tourism and foreign direct investment, but these effects are rather transient and create transference of activities to other sectors, thus cushioning the consequences.